HUBUNGAN FAKTOR SOSIAL DAN AKSESIBILITAS DENGAN KEMATIAN IBU DI KOTA BUKITTINGGI: HOSPITAL BASED 2013- 2015 - wati, Indres (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Maternal mortality rate (MMR) is the main indicator of public health status.Maternal death in Bukittinggi in the recent two years has increased significantly. Initialsurvey found that maternal death in three hospitals in 2011 were 11 cases, in 2012 11cases, in 2013 13 cases, in 2014 15 cases and until September 2015 there have been 15cases of maternal death (Hospital Annual Report).This research was case kontrol study. The population were all of pregnant women,intrapartum and postpartum women who were died in the Hospitals in Bukittinggi(Hospital based) in the period 2013-2015, as 43 cases and the population kontrol were allof intrapartum women who were registered in the Hospitals in Bukittinggi in the period2013-2015 which were 4.068 persons. Samples were 30 people with the ratio 1:1. Themain data was secondary data, namely the medical record of the health services and theresult of maternal audit from the hospitals. Data processing and analizing was donecomputerized. The result shows that there is an association between the social factordelayed in seeking aid by poor economic reason (p = 0,018 dan OR = 4,297), delayed inachieving care in health facilities because of unavailable blood (p=0.045 and OR=6,000),accessibility from living house and health services (p=0,001 and OR=10,286) andacceptance in health services (p=0,008 and OR=14,500) with maternal death. There is noassociation between delayed in reaching health facilities, infrastucture availability, andsuitability of referral service with maternal mortality. Hospitals are expected to performperiodical audit in health services in all departments, such as emergency department,oparating room and treatment room.Keyword: Social factors, accessibility, maternal mortality